Apologia poetyki - Madejski, Jerzy (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The article deals with Edward Balcerzan’s book called Pochwała poezji (Praise of poetry ) (Mikoł.w 2013). The author discusses it in the context of modern academic writing, as well as in relation to tradition and today’s autobiographical practice, but above all shows what task does structuralist poetics accomplish and how it influences the interpretation of a literary work.